5-year outcomes of transcatheter aortic valve replacement or surgical aortic valve replacement for high surgical risk patients with aortic stenosis (PARTNER 1): a randomised controlled trial. Issue 9986 (20th June 2015) - Mack, Michael J; Leon, Martin B; Smith, Craig R; Miller, D Craig; Moses, Jeffrey W; Tuzcu, E Murat; Webb, John G; Douglas, Pamela S; Anderson, William N; Blackstone, Eugene H; Kodali, Susheel K; Makkar, Raj R; et al.
Summary: Background: The Placement of Aortic Transcatheter Valves (PARTNER) trial showed that mortality at 1 year, 2 years, and 3 years is much the same with transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR) for high-risk patients with aortic stenosis. We report here the 5-year outcomes. Methods: We did this randomised controlled trial at 25 hospitals, in Canada (two), Germany (one), and the USA (23). We used a computer-generated randomisation sequence to randomly assign high-risk patients with severe aortic stenosis to either SAVR or TAVR with a balloon-expandable bovine pericardial tissue valve by either a transfemoral or transapical approach. Patients and their treating physicians were not masked to treatment allocation. The primary outcome of the trial was all-cause mortality in the intention-to-treat population at 1 year, we present here predefined outcomes at 5 years. The study is registered with ClinicalTrials.gov, number NCT00530894 . Findings: We screened 3105 patients, of whom 699 were enrolled (348 assigned to TAVR, 351 assigned to SAVR). Overall mean Society of Thoracic Surgeons Predicted Risk of Mortality score was 11·7%. At 5 years, risk of death was 67·8% in the TAVR group compared with 62·4% in the SAVR group (hazard ratio 1·04, 95% CI 0·86–1·24; p=0·76). We recorded no structural valve deterioration requiring surgical valve replacement in either group. Moderate or severe aortic regurgitation occurred in 40 (14%) of 280 patients in the TAVR group and two (1%) of 228 in the SAVR group (p<0·0001), and was associated with increased 5-year risk of mortality in the TAVR group (72·4% for moderate or severe aortic regurgitation vs 56·6% for those with mild aortic regurgitation or less; p=0·003). Interpretation: Our findings show that TAVR as an alternative to surgery for patients with high surgical risk results in similar clinical outcomes. Funding: Edwards Lifesciences.